Phytoremidation by Sansevieria sp. through absorption of Carbon Monoxide (CO) - Hari Iswoyo; Abd. Haris Bahrun; William Ganing (Agrovigor, 2023)
This study aims to determine the quality of Sansevieria plants in absorbing carbon monoxide (CO) and to determine the relationship of stomatal conditions to the quality of carbon monoxide (CO) absorption. The research was conducted in the form of a 2-factor factorial experiment using a Randomized Group Design as the environmental design. The experiment consisted of 2 factors, the first factor was the variety of Sansevieria plants consisting of three varieties, namely Sansevieria trifasciata, Sansevieria cylindrica and Sansevieria green hahnii, while the second factor was the concentration of carbon monoxide (CO) consisting of two levels, namely: the concentration of carbon monoxide released at 300 ppm and the concentration of carbon monoxide released at 800 ppm. The results showed that there was no interaction between varieties of Sansevieria plants with carbon monoxide concentrations on the quality of carbon monoxide (CO) gas absorption. The results showed no interaction between the varieties of Sansevieria plants and carbon monoxide concentrations in terms of the quality of carbon monoxide (CO) gas absorption. Sansevieria plant varieties that are given a carbon monoxide concentration of 300 ppm give the best effect on the total percentage of carbon monoxide gas absorption, which is 89.50%.